2015
DOI: 10.1371/journal.pone.0143689
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell Responses to High-Dose Methylprednisolone in Active Systemic Lupus Erythematosus

Abstract: Background/PurposeA slight increase in the proportion of circulating regulatory T (Treg) cells has been reported in systemic lupus erythematosus (SLE) patients taking oral prednisone. The effects of intravenous (IV) high dose methylprednisolone (MP) on Tregs have not yet been described, especially in active SLE.MethodsWe prospectively analyzed the proportion of circulating CD4+ Treg cell subsets defined as follows: (1) naïve Treg (nTreg) FoxP3lowCD45RA+ cells; (2) effector Treg (eTreg) FoxP3highCD45RA− cells; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 67 publications
2
24
2
1
Order By: Relevance
“…In the present study we verified the ability of various pharmacological agents with suggested modulatory effect on Treg cell development/activity: rapamycin (Fanigliulo et al 2015;Li et al 2014), prednisolone (Karagiannidis et al 2004Mathian et al 2015), atorvastatin (Forero-Peña and Gutierrez 2013), inosine pranobex, sodium butyrate (Fontenelle and Gilbert 2012), and glatiramer acetate (Haas et al 2009;Hong et al 2005) to facilitate/augment generation of iTreg cells in standard in vitro cultures, with the aim to further investigations for clinical application.…”
Section: Introductionsupporting
confidence: 74%
“…In the present study we verified the ability of various pharmacological agents with suggested modulatory effect on Treg cell development/activity: rapamycin (Fanigliulo et al 2015;Li et al 2014), prednisolone (Karagiannidis et al 2004Mathian et al 2015), atorvastatin (Forero-Peña and Gutierrez 2013), inosine pranobex, sodium butyrate (Fontenelle and Gilbert 2012), and glatiramer acetate (Haas et al 2009;Hong et al 2005) to facilitate/augment generation of iTreg cells in standard in vitro cultures, with the aim to further investigations for clinical application.…”
Section: Introductionsupporting
confidence: 74%
“…GCR has been described as an enhancer of FOXP3 gene expression . Several studies in both transplant and nontransplant fields have reported the capability of steroids to enhance Foxp3 expression in vitro and in vivo to generate Tregs . Mathian et al and Karagiannidis et al found that systemic administration of MP induced dramatic and rapid but transient increases in circulatory Tregs in patients with asthma and systemic lupus erythematosus, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While our control patients with CM also received a single dose of dexamethasone pre-operatively, we were not able to control for differences in steroid doses and duration of exposure prior to surgery in the study population. However, high-dose methylprednisolone has been shown to actually increase both the naïve and effector T regs several fold within 48 hours after treatment possibly related to increased transcription of Foxp3 following glucocorticoid receptor stimulation, that return to baseline in a week [21]. It is therefore unlikely that both the reduced number and fraction of T regs in our patients with MBL and PFT are due to higher doses of steroid exposure.…”
Section: Discussionmentioning
confidence: 91%